Square Column Structure of High Efficiency, Reliable, Uniformly Flexible LED Devices - Chih-Hao Lin; Yung-Min Pai; Chieh-Yu Kang; Huang-Yu Lin; Chun-Fu Lee; Xin-Yin Chen; Hsien-Hao Tu; Jin-Jia Yang; Cheng-Huan Chen; Chien-Chung Lin; Po-Tsung Lee; Chin-Wei Sher; et al. (Crystals, 2018)
This study demonstrates that flexible white LEDs, doped with diffusion particles and with a square column structure, have excellent luminosity, uniformity, and bending reliability. This large area (5 cm × 5 cm) square column flexible device had a smaller thickness (2 mm), and enhancements in both luminous efficiency (29.5%) and uniformity (44.6%) compared to the characteristics of the 6 mm reference sample. Optimization of the reflective layer coating for the square column, flexible white LED was achieved with a higher luminous efficiency (171 lm/w) and uniformity (92%). We designed a novel lightning bolt electrode to improve reliability and bendability. After the bending test, the blue flexible LED had a lower bending diameter (10 mm) but more bending circles (increased to 2000 times.